Tandem Mn–I Exchange and Homocoupling Processes Mediated by a Synergistically Operative Lithium Manganate. Issue 6 (8th December 2020) - Uzelac, Marina; Mastropierro, Pasquale; de Tullio, Marco; Borilovic, Ivana; Tarrés, Màrius; Kennedy, Alan R.; Aromí, Guillem; Hevia, Eva
Abstract: Pairing lithium and manganese(II) to form lithium manganate [Li2 Mn(CH2 SiMe3 )4 ] enables the efficient direct Mn–I exchange of aryliodides, affording transient (aryl)lithium manganate intermediates which in turn undergo spontaneous C−C homocoupling at room temperature to furnish symmetrical (bis)aryls in good yields under mild reaction conditions. The combination of EPR with X‐ray crystallographic studies has revealed the mixed Li/Mn constitution of the organometallic intermediates involved in these reactions, including the homocoupling step which had previously been thought to occur via a single‐metal Mn aryl species. These studies show Li and Mn working together in a synergistic manner to facilitate both the Mn–I exchange and the C−C bond‐forming steps. Both steps are carefully synchronized, with the concomitant generation of the alkyliodide ICH2 SiMe3 during the Mn–I exchange being essential to the aryl homocoupling process, wherein it serves as an in situ generated oxidant. Abstract : By exploiting chemical cooperativity between Li and Mn II, a series of symmetrical bis(aryls) has been prepared by a stepwise direct Mn–I exchange/oxidative C−C homocoupling protocol. Trapping and characterization of key reaction intermediates demonstrates the involvement of lithium manganate species in which Li and Mn work together to facilitate these transformations.